2005
DOI: 10.2320/matertrans.46.2406
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity between Sn–Ag Solder and Au/Ni–Co Plating to Form Intermetallic Phases

Abstract: For the formation of micro joint not to melt by secondary reflow soldering, we tried to enhance the reactivity of Sn-Ag solder with Au/Ni20Co plating. It was confirmed that the addition of Co in Ni and existence of Au plating effectively accelerated the reaction and the Sn-Ag solder completely transformed to the intermetallic compounds with a higher melting temperature.Particularly, the addition of Co in Ni changed the interfacial reaction layer from Ni 3 Sn 4 to (Ni,Co)Sn 2 with higher diffusivity of Ni which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A preliminary study of the Sn/Co solid/solid interfacial reaction found the formation of a distinctive cruciform pattern [7]. Though knowledge of the Sn/Co interfacial reactions is of interest to the electronic industry, only a few studies of the Sn/Co reactions [1,3,4,7,8] are available. This study thus examines reactions in the Sn/Co couples reacted at temperatures from 150 to 200 C to further understand the Sn/Co solid/solid interfacial reactions and their reaction kinetics.…”
Section: Introductionmentioning
confidence: 98%
“…A preliminary study of the Sn/Co solid/solid interfacial reaction found the formation of a distinctive cruciform pattern [7]. Though knowledge of the Sn/Co interfacial reactions is of interest to the electronic industry, only a few studies of the Sn/Co reactions [1,3,4,7,8] are available. This study thus examines reactions in the Sn/Co couples reacted at temperatures from 150 to 200 C to further understand the Sn/Co solid/solid interfacial reactions and their reaction kinetics.…”
Section: Introductionmentioning
confidence: 98%
“…Yamamoto et al have studied the interfacial reactions between Sn-Ag solder and Ni-20Co bond pads. 9 They found that the interfacial compound phase is the (Ni,Co)Sn 2 phase, rather than the common Ni 3 Sn 4 phase that forms at the solder/Ni interface. In this present work, we investigated the feasibility of using Ni-Co alloys as bond pads for Pb-free solders.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Co and Co-based alloys were evaluated as potential materials for the underbump metallurgy (UBM) of IC chips, [1][2][3][4][5] because Co has acceptable solderability and exhibits higher Young's modulus and lower intermetallic compound (IMC) growth rate during solder reaction compared with Cu and Ni, which are the common materials used for UBM. 2 In flip-chip solder joints, the Cu/solder/Co sandwich structure is encountered.…”
Section: Introductionmentioning
confidence: 99%